Influence of temperature and air velocity in obtaining flour from beef (Bos indicus) spleen, with maximum iron content - Horna , María (2022)
Iron is an important mineral element in food, being found, among other foods, in beef spleen, with high iron content. The objective of this work was to determine the temperature and speed of air drying to obtain flour with maximum iron content from beef spleen (Bos indicus L.) and to determine the physicochemical and organoleptic characteristics of the flour obtained. The beef spleen, previously selected, was washed and cut into thin slices, subjected to a tray dryer, which, in turn, were subjected to three temperatures (45, 55 and 65 ºC) and three hot air speeds (1.5, 2.5 and 3.5 m/s), followed by grinding and sieving on a 220-micron mesh. A DCA design was applied with a factorial arrangement of 3Ax3B, with 3 replicates. Iron concentration was determined using a spectrophotometer at a wavelength of 525 nm. Treatment T5 (55°C and 2.5 m/s) presented the highest iron concentration with 135.02 mg/100g, with 1.01 %; 6.13; 5.54 % and 9.94 % of acidity, pH, ash and moisture, respectively; presenting, at the same time, good organoleptic acceptability.